Posible influencia de exoplanetas sobre la actividad estelar - Flores Trivigno, Matias Gaston (2016)
The aim of this work is to analize the possible difference in the levels of activity showed by stars with and without planets. Several authors have suggested that stars with planets, in particular those with hot-Jupiter-like planets, have activity levels greater than those showed for stars of the same spectral class, but without planets. In this contribution we present the analysis of chromospheric activity indexes for 353 objects. To do so, we used high-resolution spectra (R 110 000) of F-, G-, and K-type stars taken with the High Accuracy Radial velocity Planet Searcher spectrograph, installed at the 3.6 m ESO telescope. We do no find a significant difference in the activity indexes of stars with and without planets.